Neuromuscular and metabolic responses to high-intensity intermittent cycling protocols with different work-to-rest ratios - Nicolò, A.; Bazzucchi, I.; Lenti, M.; Haxhi, J.; Scotto di Palumbo, A.; Sacchetti, M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To investigate the effects of work-to-rest-ratio manipulation on neuromuscular and metabolic responses during 2 high-intensity intermittent training (HIT) protocols to exhaustion. Since different exercise durations were expected, the authors hypothesized that the protocol registering a longer duration would have a more pronounced effect on neuromuscular responses, while the other would challenge the cardiopulmonary system more. Methods: Thirteen competitive cyclists (age 19 ± 2 y) performed a preliminary incremental test to identify their maximal power output and 2 intermittent protocols to exhaustion (40:20s and 30:30s) at a fixed work rate of 135%Pmax interspersed by passive recovery. Surface electromyographic (sEMG) parameters (including muscle-fiber conduction velocity), cardiopulmonary parameters, and blood lactate concentration [La-] were recorded. Results: Time to exhaustion and total work were significantly higher for the 30:30s (38 ± 13 min, 495 ± 161 kJ) than for the 40:20s (10 ± 3 min, 180 ± 51 kJ). No differences were found in sEMG parameters for the 2 protocols. Mean and peak values of VO2, heart rate, ventilatory parameters (except for the peak value of respiratory frequency), and [La-] were significantly higher in the 40:20s than in the 30:30s. Conclusions: These results do not support the hypothesis that a longer time spent at high intensity has a more pronounced effect on neuromuscular responses, as no differences in EMG parameters were found in the 2 HIT protocols. Regarding metabolic responses, while the 40:20s led to maximal values of VO2, [La-], and ventilatory parameters within a few minutes, the 30:30s allowed maintenance of moderately high values for a considerably longer period, especially for [La-] and ventilatory parameters.